Analisis Perencanaan dan Pengembangan Sumber Daya Manusia terhadap Kinerja Pegawai di Bank - Wanda, Nirma; Amir, Nurhikmah; Sakka, Fitriani; Ramadhan, Wahyu (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
The Influence of Human Resource Planning and Development on Bank Employee Performance. This research aims to determine the influence of human resource planning and human resource development on employee performance and to determine employee development strategies to improve employee performance. The type of research used is quantitative research. Where the population is all Bank employees, totaling 11 people. From the total population, samples were drawn using research sampling using census samples. The reason the researcher used a census sample was because the population in this study was less than 100 people, therefore the entire population became the sample. The data collection technique was carried out through a questionnaire distributed in a goggle form format via the WhatsApp application. The data analysis techniques used are validity tests and reliability tests. The results of the research will later determine whether there is an influence of human resource planning and development on the performance of bank employees